Do health sector reforms have their intended impacts? : the World Bank's Health VIII Project in Gansu Province, China - Wagstaff, Adam, 1959- 1959- (Policy research working paper, 2005)
"The literature contains few impact evaluations of health sector reforms, especially those involving broad and simultaneous changes on both the demand and supply sides of the sector. This paper reports the results of a World Bank-funded health sector reform project in China known as Health VIII. On the supply-side, the project combined infrastructure investments (especially at the township level) with improved planning and management, including a referral system between township health centers and county hospitals, and interventions aimed at improving the effectiveness and quality of care, including the introduction of clinical protocols and essential drug lists. On the demand-side, the project sought to resurrect community health insurance, and to introduce a safety net for the very poor to provide them with financial assistance with their health care expenses. The evaluation reported here concerns just one of the project's seven provinces, namely Gansu, the reason being that no suitable data are available to undertake a rigorous evaluation in all provinces. This paper makes use of a panel dataset collected for quite another purpose but whose timing (just around the time the project started and four years later) and location (covering both project and non-project counties) makes it well-suited to the task. The paper compares estimates obtained using a variety of different estimators, including na- single differences (before and after, and with and without the project), and differences-in-differences, adjusting for heterogeneity through both regression and matching methods. The results suggest that it makes a difference to the estimated impact of Health VIII which estimator is used, with the na- single differences producing often markedly different estimates from the preferred approach of combining difference-in-differences with matching.